The Diaspora and economic development in Africa - (:unkn) unknown (My University, 2018)
While the dominant collective belief asserts that brain drain is detrimental to the development of small economies, new studies hold the reverse view. This paper aims at studying the role of the Diaspora in the economic development of low-income countries with particular focus on African countries. It analyzes both the overall effect and the specific effect of emigration according to the level of education of emigrants. While the empirical results for all developing countries fail to establish an unambiguous relationship between the Diaspora and economic development, those concerning African countries establish a clear and unambiguous relationship. The African Diaspora, especially the high-skilled Diaspora, contributes positively, significantly and robustly to the improvement of income in Africa. These findings challenge the dominant collective belief. Improvements in human capital, total factor productivity and democracy are effective transmission channels of this impact. In addition, while high-skilled emigrants have an overall greater impact on economic development and democracy, those with a low level of education contribute more to remittances to Africa.
Keywords: African Research